Accelerated partial breast irradiation using intensity modulated radiotherapy versus whole breast irradiation: Health-related quality of life final analysis from the Florence phase 3 trial. (May 2017) - Meattini, Icro; Saieva, Calogero; Miccinesi, Guido; Desideri, Isacco; Francolini, Giulio; Scotti, Vieri; Marrazzo, Livia; Pallotta, Stefania; Meacci, Fiammetta; Muntoni, Cristina; Bendinelli, Benedetta; Sanchez, Luis Jose; et al.
Abstract: Background: Accelerated partial breast irradiation (APBI) represents a valid option for selected early breast cancer (BC). We recently published the 5-year results of the APBI-IMRT-Florence phase 3 randomised trial (NCT02104895 ), showing a very low rate of disease failure, with acute and early–late toxicity in favour of APBI. We present the early and 2-year follow-up health-related quality of life (HRQoL) results. Methods: Eligible patients were women aged more than 40 years with early BC suitable for breast-conserving surgery. APBI consisted of 30 Gy in five fractions delivered with IMRT technique. Standard whole breast irradiation (WBI) consisted of 50 Gy in 25 fractions plus a 10 Gy in five fractions boost on tumour bed. A total of 520 patients were enrolled in the phase 3 trial. Overall, 205 patients (105 APBI and 100 WBI) fully completed all the given questionnaires and were therefore included in the present analysis. As HRQoL assessment, patients were asked to complete the European Organisation for Research and Treatment of Cancer QLQ-C30, and the BR23 questionnaires at the beginning (T0), at the end (T1) and after 2 years from radiation (T2). Findings: No significant difference between the two arms at QLQ-C30 and BR23 scores emerged at T0. Global health status (p = 0.0001), and most scores of the functional and symptom scales of QLQ-C30 at T1 showed significant differences in favour of the APBI arm. Concerning the BR23 functional and symptom scales, the body image perception, future perspective and breast and arm symptoms were significantly better in the APBI group. Similar significant results emerged at T2: significant differences in favour of APBI emerged for GHS (p = 0.0001), and most functional and symptom QLQ-C30 scales. According to QLQ-BR23 module, among the functional scales, the body image perception and the future perspective were significantly better in the APBI group (p = 0.0001), whereas among the symptom scales significant difference emerged by breast and arm symptoms with better outcomes in APBI arm (p < 0.01). Interpretation: Early BC treated with APBI showed an improved short-term, and 2-year follow-up HRQoL outcome as compared with WBI. Early BC treated with APBI showed an improved short-term, and 2-year follow-up HRQoL outcome as compared with WBI. APBI should be strongly considered in the treatment choice for selected low-risk patients. Mature local control results from ongoing adequately powered randomised trials are awaited. Highlights: Accelerated partial breast irradiation (APBI) represents a valid option for selected early breast cancer. APBI showed an improved short-term, and 2-year follow-up health-related quality of life outcome as compared with whole breast irradiation. APBI should be strongly considered in the treatment choice for selected low-risk patients.